Digital Literacy Skills in the Study of Tafsir Al-Mishbah by M. Quraish Shihab - Arifin, Mohamad Zaenal; Ma'rufatun, Ma'rufatun; Hikam, Ahmad Bahrul; Fata, Badrus Samsul (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This study discusses the scope of digital literacy studied based on Tafsir al-Mishbah. The goal is to find the verses that indirectly explain digital literacy. That way, it will produce a theory on using digital media from an Islamic point of view. So that the Muslim generation, in particular, can keep pace with technological developments and digital literacy capabilities. This research method uses qualitative research with a library research approach. The primary reference is based on Tafsir al-Mishbah, equipped with books and accredited journals. Through this method, it can be found how to explain the verses of the Qur'an about the concept of digital literacy. The study found that terms related to digital literacy can be expressed through the terms iqra', kitabah, and qalam. Furthermore, the principles of digital literacy in Tafsir al-Mishbah are also found, including the use of digital media (QS. al-Qalam: 1, QS.  al-Alaq: 1); the use of digital media (QS. al-Baqarah: 263, QS. al-Isra: 28, QS.  an-Nisâ: 9 and 63); information selection (QS. al-Hujurât: 6, QS. an-Nūr: 11); content dissemination (QS.  al-Hujurât: 12, QS. an-Nūr: 15); maintaining privacy (QS. an-Nūr: 27-28); and creativity in creating content (QS. Hūd: 37). It can be concluded that the concept of digital literacy according to the Qur'an is a means of goodness, a means of communicating by meeting the requirements of Islamic principles, a means of researching and selectively receiving information, a means of spreading hoax news, advice on maintaining personal data, and as a means of developing creativity in content. These Islamic principles can improve a person's digital literacy competence to keep up with the increasingly rapid development of technology.